The participation of indigenous communities in the War of the Pacific (1881-1884). Historiographic analysis and research perspectives (1979-2020) - Abanto Chani, Julio César (2022)
The objective of this article is to highlight the role of indigenous communities in the construction of an idea of an alternative nation, which emerged in the midst of the War of the Pacific, particularly during the worsening of the armed conflict: between the fall of Lima (1881) and the signing of the Treaty of Ancón (1883). For this, we will rely on a historiographical journey with the contributions and the follow-up to the trajectory of the discussion of various positions that shows us its beginnings, the current panorama and the future perspectives on this subject. In this way, we will analyze various studies carried out by researchers Heraclio Bonilla, Florencia Mallon, Nelson Manrique, Mark Turner, Nelson Pereyra, Hugo Pereyra and Brooke Larson, among others. Finally, we will evaluate the production of university theses on the war with Chile in the last two decades to identify the level of incidence of peasant communities within historical studies.